Nutritional, health and environmental dimensions of Swiss food consumption trends - Reguant-Closa, Alba; Loginova, Daria; Mehner, Eric; Mann, Stefan; Nemecek, Thomas (Frontiers in Nutrition, 2025)
IntroductionFood has a considerable environmental impact beyond its effects on the nutritional and health status of the population. Food consumption changes over time and is influenced by diverse socioeconomic factors. This study aimed to evaluate the nutritional, health, and environmental (NHE) dimensions of foods commonly consumed by the Swiss population, assess consumption trends in combination with the NHE dimensions from 1990 to 2017 at the food and diet levels, and suggest recommendations for consumption pattern improvement.MethodsThe nutrient rich food index 10.3 (NRF10.3) was used to evaluate the nutritional dimension, while the health nutritional index (HENI) evaluated the health effects of dietary intake. The environmental dimension of the foods was assessed by LCA using the SALCA method v2.0.1. To evaluate consumption trends, we used data on Swiss household-level purchases provided by the Swiss Federal Statistical Office for the years 1990, 2000, 2010, and 2017. Using regression analysis, we estimated the trends of NHE dimensions combined with consumption at the productand household diet levels.ResultsThe analysis showed many trades-offs between the dimensions. At the food group level, the decreased consumption of all meat except poultry had a positive nutritional and health impact while decreasing theoverall environmental impact of meats. At the diet level, an increase in nutritional density was observed over time, while the HENI index was higher in 2000. The environmental dimension was highly dependent on which impact category was observed.DiscussionThree main recommendations can be drawn from this study: First, it is important to include several dimensions in food and diet analysis. Second, decreasing red and processed meat and increase of poultry consumption through the years can maintain the nutrient density of the diets, improve its health impacts, and decrease the majority of the environmental impact categories compared to diets with high red meat consumption. Third, the consumption of pulses, fruits, vegetables, and nuts was very low compared to the recommendations, but increasing it can improve all the dimensions studied.